2020
DOI: 10.1186/s12884-020-03157-7
|View full text |Cite
|
Sign up to set email alerts
|

The combination of symphysis-fundal height and abdominal circumference as a novel predictor of macrosomia in GDM and normal pregnancy

Abstract: Background: Macrosomia is a major adverse pregnancy outcome of gestational diabetes mellitus (GDM). Although BMI, symphysis-fundal height (SFH) and abdominal circumference (AC) are associated with foetal weight, there are some limitations to their use, especially for the prediction of macrosomia. This study aimed to identify a novel predictive methodology to improve the prediction of high-risk macrosomia. Methods: Clinical information was collected from 3730 patients. The association between the ISFHAC (index … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…What is striking in this study is the high rate of emergency and non-elective caesarean section testifying of the late detection of macrosomia, probably during labor. This reinforces the need for good clinical follow-up by regular measurement of symphysis fundal height associated to abdominal circumference [21]. In addition, the absence of influence of third term ultrasonography to predict macrosomia in our study is consistent with previous reports in the literature and emphasizes the need to use a multiparametric ultrasound model including umbilical vein flow for optimal performance and accuracy to diagnose macrosomia [22] [23].…”
Section: Discussionsupporting
confidence: 91%
“…What is striking in this study is the high rate of emergency and non-elective caesarean section testifying of the late detection of macrosomia, probably during labor. This reinforces the need for good clinical follow-up by regular measurement of symphysis fundal height associated to abdominal circumference [21]. In addition, the absence of influence of third term ultrasonography to predict macrosomia in our study is consistent with previous reports in the literature and emphasizes the need to use a multiparametric ultrasound model including umbilical vein flow for optimal performance and accuracy to diagnose macrosomia [22] [23].…”
Section: Discussionsupporting
confidence: 91%
“…Studies have demonstrated that pregnant women complicated with GDM are more likely to deliver macrosomia [ 29 , 30 ]. However, in the current study, we demonstrated that GDM was not significantly associated with the risk of macrosomia in multipara, which might be due to the One-Day Care Clinic for pregnancies with GDM in our study centers.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is a common complication during pregnancy, and macrosomia is one of the major adverse pregnancy outcomes of GDM ( 1 ). Insulin-like growth factor 2 (IGF2) encodes a polypeptide that is abundant in fetal tissues and circulation ( 2 ), is usually expressed in fetal tissue and invasive trophoblast cells at the placental maternal-fetal interface ( 3 ) and is the major insulin-like growth factor that plays a growth-promoting role during the process of embryonic development ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%